Strategi Komunikasi Pemasaran Umkm (Usaha Mikro Kecil Menengah) Kacang Ting-Ting Dalam Menarik Minat Konsumen Di Kenten Jl. Tanjung Harapan Lr. Kenanga Kel. Bukit Sangkal Palembang - Dika Wijaya; Muhammad Randicha Hamandia; Fifi Hasmawati Wijaya (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
This research is entitled Marketing Communication Strategy for MSMEs (Micro, Small and Medium Enterprises) Peanut Ting-Ting in Attracting Consumer Interest in Kenten Jl. Cape of Good Hope Lr. Memories Ex. Sangkal Hill, Palembang. Indonesia is one of the largest countries in the world. Where in Indonesia there are various MSMEs (Micro Small and Medium Enterprises) Marketing Communication Strategies in buying and selling transactions, one of which is the MSME (Micro Small and Medium Enterprises) Marketing Communication Strategy in Marketing Ting-Ting Peanuts in Kenten Jl. Cape of Good Hope Lr. Memories Ex. Bukit Sangkal Palembang In Attracting Buyer's Interest. The formulation of the problem is How is the MSME (Micro, Small and Medium Enterprises) Marketing Communication Strategy in Marketing Ting-Ting Peanuts in Kenten Jl. Cape of Good Hope Lr. Memories Ex. Bukit Sangkal Palembang In Attracting Buyers Of Ting-Ting Peanuts?. The research method used is a type of field research with a qualitative approach through the types and sources of data obtained from direct interviews with the owner of the ting-ting peanuts, as well as the ting-ting peanut customers in the kenten area of ​​Palembang city as well as documentation in the field and materials. research materials sourced from books, journals and other documents related to research. The results of this study are that of the 8 existing marketing communication strategies, the marketing communication strategy carried out by UMKM Kacang Ting-Ting is not good because it still uses the direct selling method, namely sales by coming directly entrusting to stalls with a traditional direct mechanism. So of course the scope for sales is still relatively small with the use of capital that is not too large, only limited to the scope around the Ting-Ting Peanuts MSME area. The reason for the UMKM Kacang Ting-Ting not to use social media or mass media is because according to the seller, they don't know much about technology and according to him, sales through social media have a larger scope, while the capital currently used is not too large, with sales only limited to areas that can be only be reached because they do use a mechanism to directly come to small shops.